The Price of Change: Assessing the Cost of Compensation Reduction on Employee Turnover and Productivity (Journal of Social Sciences Review, 2023)
This study investigates the impact of Compensation Reduction on employee productivity and turnover intentions in Punjab, Pakistan's TEVT sector, considering the moderating role of fairness and equality perception. A sample of N=1200 TEVT employees was surveyed via structured questionnaires from March to July 2023. Utilizing smarPLS4, the study analyzed Compensation Reduction's influence on Employee Productivity and Turnover Intentions, mediated by Job Embeddedness while moderated by the Perception of Fairness and Equality. Results reveal Compensation Reduction's adverse effect on job embeddedness, reducing affiliations and productivity, and increasing turnover intentions. The TEVT sector faces high turnover and low productivity, necessitating equitable compensation policies. This study highlights the substantial organizational cost of losing intellectual assets due to reduced fairness. By focusing on Job Embeddedness and proposing strategies for retention, it offers insights for effective compensation policies. Uniquely pioneering in Punjab's TEVT sector, it underscores fairness and equality's crucial role in retaining intellectual capital. Future research should extend the analysis to other sectors to optimize organizational intellectual resources.
Keywords: Compensation Reduction; Perception of Fairness & Equality; Job Embeddedness; Employee Productivity; Turnover Intentions